The Role of Program Directors in Treatment Practices: The Case of Methadone Dose Patterns in U.S. Outpatient Opioid Agonist Treatment Programs - Frimpong, Jemima A. (Health Serv Res, 2016)
OBJECTIVE: To describe changes in characteristics of directors of outpatient opioid agonist treatment (OAT) programs, and to examine the association between directors’ characteristics and low methadone dosage. DATA SOURCE: Repeated cross‐sectional surveys of OAT programs in the United States from 1995 to 2011. STUDY DESIGN: We used generalized linear regression models to examine associations between directors’ characteristics and methadone dose, adjusting for program and patient factors. DATA COLLECTION: Data were collected through telephone surveys of program directors. PRINCIPAL FINDINGS: The proportion of OAT programs with an African American director declined over time, from 29 percent in 1995 to 16 percent in 2011. The median percentage of patients in each program receiving <60 mg/day declined significantly, from 48.5 percent in 1995 to 29 percent in 2005 and 23 percent in 2011. Programs with an African American director were significantly more likely to provide low methadone doses than other programs. This association was even stronger in programs with an African American director who served populations with higher percentages of African American patients. CONCLUSIONS: Demographic characteristics of OAT program directors (e.g., their race) may play a key role in explaining variations in methadone dosage across programs and patients. Further research should investigate the causal pathways through which directors’ characteristics affect treatment practices. This may lead to new, multifaceted managerial interventions to improve patient outcomes.